2016
DOI: 10.1177/0033294116667092
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Endocrinology and Musth Indicators in a Captive Asian Elephant (Elephas maximus)

Abstract: Even in the best situations, the artificial social constructs of captivity alter natural elephant behavior and unfortunately create distress. Asian elephants are powerful and intelligent animals that require consideration for their well-being and prudent management. The males present particular difficulties due to a temporary state of heightened aggressive behavior unique to male elephants called "musth." When he is in this state, the danger the elephant poses to other animals and the people around him is cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…This was confirmed by the finding that use of hooks was not associated with years of camp operation or the type of work elephants were involved in. However, new camps were less likely, or perhaps less willing, to have bull elephants on site because of the increased danger they pose because of musth, a temporary state of heightened aggressive and unpredictable behavior in association with elevated testosterone ( Duer, Tomasi & Abramson, 2016 ). Overall, compared to earlier surveys, elephant management practices appear to have improved, which could signal a positive trend toward improving animal care.…”
Section: Discussionmentioning
confidence: 99%
“…This was confirmed by the finding that use of hooks was not associated with years of camp operation or the type of work elephants were involved in. However, new camps were less likely, or perhaps less willing, to have bull elephants on site because of the increased danger they pose because of musth, a temporary state of heightened aggressive and unpredictable behavior in association with elevated testosterone ( Duer, Tomasi & Abramson, 2016 ). Overall, compared to earlier surveys, elephant management practices appear to have improved, which could signal a positive trend toward improving animal care.…”
Section: Discussionmentioning
confidence: 99%
“…In free-ranging African elephants in the Amboseli National Park, DNA analysis revealed that 74% of sires were in musth at the time of conception (Hollister-Smith et al 2007). In a study on captive Asian elephants in the USA, no correlation between the onset of musth and the onset of oestrus was found (Duer et al 2016), but Dow et al (2011) measured slightly higher cyclicity rates (by approximately 11%) in female African elephants in facilities housing a bull than in those without a bull.…”
Section: Intraspecific Interactionsmentioning
confidence: 98%
“…In a study on captive Asian elephants in the USA, no correlation between the onset of musth and the onset of oestrus was found (Duer et al. ), but Dow et al. () measured slightly higher cyclicity rates (by approximately 11%) in female African elephants in facilities housing a bull than in those without a bull.…”
Section: Factors Influencing Reproduction In Free‐ranging Semi‐captimentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that data or behavior ratings by observers who are familiar with the individual animals, such as their caretakers, tend to be reliable and valid (Gosling, , ; Meagher, ). Keeper‐centric data collection frameworks have taken a variety of forms, often tailored to the resources and the most pressing questions related to species management, and have been applied to a wide range of species including black rhinoceros ( Diceros bicornis ; Carlstead et al, ); cheetah ( Acinonyx jubatus ; Wielebnowski, ); gorilla ( Gorilla gorilla gorilla ; Less, Kuhar, Dennis, & Lukas, ); and Asian elephant ( Elephas maximus ; Duer, Tomasi, & Abramson, ). Robinson et al (, ) demonstrated that keeper questionnaires can be a useful tool in collecting data on animal welfare and personality.…”
Section: Introductionmentioning
confidence: 99%